Civil Society Elites: A Research Agenda - Johansson, Håkan; Uhlin, Anders (Politics and governance, 2020)
This editorial introduces the thematic issue on ‘civil society elites,’ a topic that has been neglected in elite research as well as civil society studies. It elaborates on the concept of ‘civil society elites’ and explains why this is an important emerging research field. By highlighting different methodological approaches and key findings in the contributions to the thematic issue, this article aims at formulating an agenda for future research in this field.